Factors Affecting Role of Women in Various Agricultural Activities with Special Reference to Crop Diversification in Haryana (International Journal of Environmental Sciences, 2025)
With the advent of Green Revolution, there was a substantial growth in agriculture sector of Haryana. However, over the years, the increased production and penchant of farmers towards paddy and wheat cultivation gave rise to numerous problems. The crop specialization started affecting the environment negatively, resulting into its degradation and eventually impacting the human health. Crop diversification might be helpful in addressing these concerns and can possibly be a breakthrough in overcoming the slumping agricultural economy. Women are involved in multifarious activities ranging from household chores to agricultural and domestication tasks. Their empowerment can help in largely diversifying the crops. This paper endeavors to identify the factors affecting the role of women in various agricultural activities with reference to crop diversification in Haryana. The researchers used primary data for this purpose and analysed the data by using the Logistic Regression Analysis in the study. The study revealed that education, head of households, ownership of land holding, and land cultivated by the households are the statistically significant factors that can affects the participation of women in decision-making regarding various agricultural activities with special reference to crop diversification in the state.